(untitled) (International Journal of Communication Systems and Network Technologies, 2021)
Ferrocement is one of the cement based composites used for retrofitting and rehabilitation among many applications. One of the foremost factors affecting the durability of ferrocement is the corrosion of wire meshes. This problem is magnified in corrosive environments. With the passage of time, the effective strength of the wires is reduced due to a reduction in diameter and deterioration of the bond between the matrix and the reinforcement. In the present study, an attempt has been made to improve the corrosion resistance of the metallic wire meshes used in ferrocement with corrosion inhibitors. Two corrosion inhibitors, viz. Calcium Nitrite and Tannic Acid, were used. Weight loss studies and potentio-dynamic polarization tests were conducted in saline water medium. Corrosion efficiency and corrosion rate were calculated. At a 1% dose, both the inhibitors, when applied in a slurry coated form, were found to be sufficiently effective in controlling the corrosion. The effect of these corrosion inhibitors on compressive strength of cement sand mortar was also observed. The high efficiency and low corrosion rate exhibited by both the inhibitors proves their potential in controlling the corrosion. The electrochemical tests also confirm these findings. Compressive strength test also suggest that these inhibitors do not have any significant adverse effect on the mechanical properties of mortar mix. Long term studies are needed to make final recommendations with regard to the dose of these inhibitors for the protection of steel wire mesh reinforcement in ferrocement. One of the foremost factors affecting the durability of ferrocement is the corrosion of wire meshes. This problem is magnified in corrosive environments. With the passage of time, the effective strength of the wires is reduced due to a reduction in diameter and deterioration of the bond between the matrix and the reinforcement. In the present study, an attempt has been made to improve the corrosion resistance of the metallic wire meshes used in ferrocement with corrosion inhibitors. Two corrosion inhibitors, viz. Calcium Nitrite and Tannic Acid, were used. Weight loss studies and potentio-dynamic polarization tests were conducted in saline water medium. Corrosion efficiency and corrosion rate were calculated. At a 1% dose, both the inhibitors, when applied in a slurry coated form, were found to be sufficiently effective in controlling the corrosion. The effect of these corrosion inhibitors on setting time of cement, pH, and compressive strength of cement sand mortar were also observed.